2020
DOI: 10.1002/jmor.21148
|View full text |Cite
|
Sign up to set email alerts
|

Skull osteology and osteological phylogeny of the Western whip snake Hierophis viridiflavus (Squamata, Colubridae)

Abstract: The skull osteology of Hierophis viridiflavus is here described and figured in detail on the basis of 18 specimens. The sample includes specimens from the ranges of both Hierophis viridiflavus viridiflavus and Hierophis viridiflavus carbonarius as well as specimens not identified at This article is protected by copyright. All rights reserved. This is the author manuscript accepted for publication and has undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…To accomplish this, we present herein the first thorough osteological description and illustration of any species within the Atractaspididae, based on fully segmented micro-computed tomography (micro-CT) imagery of the skull of Atractaspis irregularis (Reinhardt, 1843) (Figures 1-9, Figures S1-S23). This study thus contributes to a recently growing body of anatomical research using micro-CT data to examine un-or under-described snake taxa (e.g., Rieppel and Maisano, 2007;Rieppel et al, 2009;Olori and Bell, 2012;Palci et al, 2016;Chretien et al, 2019;Strong et al, 2019;Racca et al, 2020). This research approach provides an essential foundation for constructing higher-order hypotheses of organismal evolution and phylogenetic relationships and is particularly important for understanding complicated but evolutionarily significant structures such as the skull.…”
Section: Despite This Morphological Novelty Osteological Descriptions Ofmentioning
confidence: 93%
See 1 more Smart Citation
“…To accomplish this, we present herein the first thorough osteological description and illustration of any species within the Atractaspididae, based on fully segmented micro-computed tomography (micro-CT) imagery of the skull of Atractaspis irregularis (Reinhardt, 1843) (Figures 1-9, Figures S1-S23). This study thus contributes to a recently growing body of anatomical research using micro-CT data to examine un-or under-described snake taxa (e.g., Rieppel and Maisano, 2007;Rieppel et al, 2009;Olori and Bell, 2012;Palci et al, 2016;Chretien et al, 2019;Strong et al, 2019;Racca et al, 2020). This research approach provides an essential foundation for constructing higher-order hypotheses of organismal evolution and phylogenetic relationships and is particularly important for understanding complicated but evolutionarily significant structures such as the skull.…”
Section: Despite This Morphological Novelty Osteological Descriptions Ofmentioning
confidence: 93%
“…The dentary of Atractaspis is quite unique compared to other, non- Scanferla, 2016;Strong et al, 2019;Racca et al, 2020).…”
Section: Dentarymentioning
confidence: 98%
“…Another feature of the maxilla of Hypoptophis that warrants discussion is the apposition of the palatine process and the ectopterygoid process. In most colubroids having both processes, the medially expanded ectopterygoid process is located farther back, separated from the palatine process (another medial expansion) by a narrower stretch of maxillary shaft (e.g., the maxilla of the colubrid Hierophis described by Racca et al, 2020 ). In Aparallactines, barring the centipede eating Aparallactus spp., the ectopterygoid process is separated from the palatine process merely by a notch (Figure S3 ).…”
Section: Discussionmentioning
confidence: 99%
“…carbonarius, the melanic morphotype, occurs throughout Italy (except the northwestern part and including Sicily), in Slovenia and Croatia. This morphotype is thought to have emerged after a vicariant speciation event (Racca et al, 2020), hypothetically caused by a combination of glacial, tectonic and eustatic factors during the Pleistocene (Mezzasalma et al, 2015). Although both morphotypes have been commonly treated in the literature as subspecies, Mezzasalma et al (2015) proposed to elevate H. v. subsp.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, a study conducted by Gramolini et al (2018) found that gene flow occurred within an area where the two taxa came into contact, refuting the recent assignment of Hierophis carbonarius. Since then, the two morphotypes are still considered subspecies (Racca et al, 2020;Gramolini et al, 2018).…”
Section: Introductionmentioning
confidence: 99%